2020
DOI: 10.17537/2020.15.20
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model Linking Ca2+-Dependent Signaling Pathway and Gene Expression Regulation in Human Skeletal Muscle

Abstract: The physiological adaptation to aerobic endurance exercises is provided by activation of signaling pathways in skeletal muscle cells. Training-induced activation of specific signaling pathways results in significant transcriptional responses. Despite the ongoing endeavours to experimentally investigate regulatory mechanisms and signal transduction pathways involved in the contraction-induced adaptation, quantitative contribution of certain signal molecules in expression regulation of genes responsible for intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…To put these pieces into a single picture, mathematical modeling seems to be a perspective approach. For this purpose, we have started to develop a complex mathematical model that links metabolic changes with the expression of some exercise-induced genes (namely NR4A2 , NR4A3 and PPARGC1A ) [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…To put these pieces into a single picture, mathematical modeling seems to be a perspective approach. For this purpose, we have started to develop a complex mathematical model that links metabolic changes with the expression of some exercise-induced genes (namely NR4A2 , NR4A3 and PPARGC1A ) [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings drove us to include in our model the Ca 2+ -dependent regulation of calmodulin, CREB1 (via CaMKII), CRTC (via calcineurin), and AMPK (via CaMKK2) (Figure 3). The amount of these proteins in human skeletal muscle was estimated using published proteomics and transcriptomics data (Murgia et al, 2017; Popov et al, 2019) ( see Supplementary data in (Akberdin et al, 2020)).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in a genome-wide study on various human tissues, it was shown that the phosphorylation level of CREB Ser133 does not always correlate with its transcriptional activity (Zhang et al, 2005). Therefore, we suggested the expression of genes with delayed response (including PPARGC1A ) is regulated by increasing the expression of one of the early response genes encoding transcription factors leading to a rapid increase of corresponding protein (see Figure 1 and Figure 5 in (Akberdin et al, 2020). Analysis of contractile activity-specific transcriptomic data (Popov et al, 2019) showed that a rapid increase in the expression of genes encoding various TFs is observed already in the first hour after an exercise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model has been developed using a modular approach where an investigated process or biological phenomenon is considered via combination of its subsystem’s models. This approach is widely used to construct diverse models of biological systems ( Kurata et al, 2014 ; Likhoshvai et al, 2014 ; Kazantsev et al, 2018 ; Kiselev et al, 2019 ; Akberdin et al, 2020 ). The model of a large ecosystem consists of two subsystems.…”
Section: Model Of Evolutionary Self-development Of a Large Ecosystemmentioning
confidence: 99%